Albumin competitively inhibits glycation of less abundant proteins - Bhonsle, Hemangi S.; Singh, Sameer Kumar; Srivastava, Ghanshyam; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Protein and Peptide Letters, 2008)
Glycation, a non-enzymatic reaction between glucose and protein is the primary cause of diabetic complications. Albumin, the most abundant plasma protein undergoes glycation both in vivo and in vitro. The influence of albumin on glycation of less abundant proteins has not been addressed. For the first time, we show that albumin competitively inhibits the glycation of less abundant proteins. This study suggests that at least in the initial stages of diabetes, albumin may protect other proteins from glycation.
Keywords: Diabetes; glucose; insulin; MALDI-TOF-MS; vascular complication

Molecular investigation of glycated insulin-induced insulin resistance via insulin signaling and AGE-RAGE axis - Walke, Prachi B.; Bansode, Sneha B.; More, Nikita P.; Chaurasiya, Arvindkumar H.; Joshi, Rakesh S.; Kulkarni, Mahesh J. (Biochimica ET Biophysica Acta-Molecular Basis of Disease, 2021)
Hyperglycemic condition in diabetes promotes glycation of various plasma proteins including insulin. Glycation of insulin has been reported to reduce its biological activity. Reduced biological activity of glycated insulin could be either due to reduced affinity for the insulin receptor and impaired insulin signaling, or it can act as a ligand for the receptor for advanced glycation end products (RAGE) and activates oxidative stress and pro-inflammatory pathways leading to insulin resistance. This study investigates the effect of glycated insulin on both insulin and RAGE signaling. Glycated insulin treatment to Chinese hamster ovary (CHO-IR-GLUT4) cells stably expressing insulin receptor (IR) and glucose transporter fused with a green fluorescent protein (GLUT4-GFP) resulted in the impairment of insulin signaling, as the phosphorylation of IR and AKT significantly reduced, which affected GLUT4 translocation and glucose uptake. Moreover, it also activated RAGE signaling as observed by increased expression of NADPH oxidase accompanied by an increase in reactive oxygen species (ROS). Immunofluorescence study indicated the translocation of NF-kappa B to the nucleus upon treatment of glycated insulin. This was associated with increased RAGE expression, Caspase 3, and cell death. Downregulation of RAGE with the losartan treatment restored the impaired insulin signaling and glucose uptake. Additionally, in silico study demonstrated that glycated insulin has reduced binding affinity to insulin receptor and increased binding affinity to RAGE. Overall, this study demonstrates the role of glycated insulin in exacerbating insulin resistance by impairing insulin signaling as well as stimulating AGE-RAGE signaling.
Keywords: AGE; Diabetes; Glycation; Hyperglycemia; insulin; RAGE

Characterization of S-homocysteinylation of Human Insulin and Its Implications in Diabetes - Sheikh, Amreen B.; Jathar, Swaraj M.; Tammara, Vaishnavi; Das, Atanu; Kulkarni, Mahesh J. (Protein Journal, 2025)
Homocysteine thiolactone is a reactive thiol known for its interaction with various proteins. Nevertheless, there exists a paucity of information concerning the interaction between homocysteine thiolactone and human insulin, particularly regarding the mechanism by which homocysteine facilitates the reduction of disulfide bonds within insulin. In the present study, we have elucidated the binding sites of homocysteine to the cysteine residues (A6-B7 and A20-B19) that are implicated in the formation of intermolecular disulfide bonds in insulin through an in vitro reaction analyzed via LC-ESI MS/MS. This results in a reduction of disulfide bonds linking the A and B chains, which was corroborated by MALDI-TOF-MS and ESI-MS analysis. The secondary structure of insulin is affected by this modification, as evidenced by circular dichroism spectroscopy. In-silico studies also show that homocysteine affects the insulin structure. A glucose uptake assay conducted in Chinese hamster ovary (CHO) cells that stably express the insulin receptor revealed that HC-modified insulin is less effective in inducing glucose uptake compared to native insulin, suggesting that HC-induced structural modifications in insulin influence functional activity. This study provides insight into the HC-induced structural and functional changes in insulin and discusses the consequent implications for diabetes.
Keywords: Disulfide bonds; Homocysteinylation; insulin; Mass spectrometry

Simple freeze-thaw based method for efficient purification of recombinant human proinsulin from inclusion bodies - Rajesh, S.; Jathar, Swaraj; Banarjee, Reema; Sharma, Monika; Palkar, Shivani; Shankar, S. Shiva; Kulkarni, Mahesh J. (Protein Expression and Purification, 2025)
Insulin is a pivotal peptide hormone essential for regulating glucose homeostasis. It has been known for over 100 years, but its production and purification methods are still under improvement. Escherichia coli based bacterial expression system is primarily used for insulin production. The human insulin protein expressed in bacteria usually forms inclusion bodies, complicating the purification process. Traditionally, insulin purification is a timeconsuming process involving urea-based denaturation methods, and various refolding techniques, followed by extensive chromatographic methods. Here, we report an easy and efficient purification of human proinsulin involving freeze-thaw based solubilization method. The extracted proinsulin inclusion bodies are treated with different concentrations of urea, followed by a freeze-thaw based solubilization. The freezing was carried out at various temperatures, mainly -80 degrees C, -20 degrees C, and -196 degrees C to determine the optimum condition for solubilization. Highest solubilization of proinsulin from the inclusion body was achieved with 0.5M urea and -20 degrees C. Further Nickel NTA-based purification was performed, and the purified protein was characterized for disulfide mapping by high-resolution mass spectrometer (HRMS). We also performed glucose uptake assays to validate the functional properties of purified proinsulin. This freeze-thaw based mild solubilization approach is a fast and effective method for getting bioactive proinsulin, which will help further design better purification and processing strategies for insulin production.
Keywords: Diabetes; Disulfide mapping; glucose; insulin; Mass spectrometry